Marketing Mix and Performance of Manufacturing Small Medium Sized Enterprises (SMES) in Kedah and Perlis - Nasiruddin, Haron (2011)
Despite the importance of marketing to small and medium-sized enterprises (SMEs), the review of the small business literature indicates that marketing in SMEs has not only received limited research attention but also neglected, particularly in the Malaysian context. This study initiated an attempt to examine the relationship between marketing mix and performance of SMEs. More specifically, the study attempted to investigate the relationships between product, price, place, promotion and performance of manufacturing SMEs in the states of Kedah and Perlis. The data for the study was collected by using a structured questionnaire. A total of 250 questionnaires were mailed to selected owners and managers of SMEs in Kedah and Perlis. Of the total 250 questionnaires mailed, 53 respondents completed and returned the questionnaires. Pearson Correlation analysis was used to test the relationship between the marketing mix and the performance of the SMEs that participated in this study. As a whole, the results of the study indicated the following: i. There was partial positive relationship between product and performance of SMEs; ii. No significant relationship was found between price and performance of SMEs; iii. There was partial positive relationship between place and performance of SMEs; and iv. There was partial positive relationship between promotion and performance of SMEs.